2019
DOI: 10.1016/j.jaerosci.2019.105437
|View full text |Cite
|
Sign up to set email alerts
|

Airborne disinfection using microwave-based technology: Energy efficient and distinct inactivation mechanism compared with waterborne disinfection

Abstract: A B S T R A C TMicrowave has been extensively applied to inactivate microorganisms in liquids, food, and surfaces. However, energy efficiency is a limiting factor for the environmental application. The utilization pathway and energy efficiency of the microwave in different media have not been investigated. In this study, the inactivation performance, energy utilization, and bactericidal mechanisms for microwave-irradiated airborne and waterborne Escherichia coli were compared. A Beer-Lambert law-based model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…In addition, MW irradiation degraded endotoxins, achieving a 35% removal efficiency when the temperature increased to 200°C. In a further study ( Wang et al, 2019a ), MW irradiation showed nearly 20 times the inactivation rate of airborne E. coli than of waterborne E. coli , which was because water absorbed most of the MW energy (92.3%) to increase the temperature rather than kill bacteria. The more absorbed energy could be used to inactive airborne bacteria.…”
Section: Application Of Microwaves In Controlling Bacteriamentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, MW irradiation degraded endotoxins, achieving a 35% removal efficiency when the temperature increased to 200°C. In a further study ( Wang et al, 2019a ), MW irradiation showed nearly 20 times the inactivation rate of airborne E. coli than of waterborne E. coli , which was because water absorbed most of the MW energy (92.3%) to increase the temperature rather than kill bacteria. The more absorbed energy could be used to inactive airborne bacteria.…”
Section: Application Of Microwaves In Controlling Bacteriamentioning
confidence: 91%
“…However, their ability to eliminate bacterial infections has not received enough attention. MW as a component of the electromagnetic spectrum, are non-ionizing radiation with frequencies ranging from 300 MHz to 300 GHz, and wavelengths between 1 m and 1 mm ( Mawioo et al, 2016 ; Wang et al, 2019a ; Shaw et al, 2021 ). The effects of MW include thermal and non-thermal ( Rougier et al, 2014 ; Shaw et al, 2021 ), and it is generally believed that the temperature increase caused by MW exposure plays a key role in microorganism inactivation ( Rougier et al, 2014 ; Shaw et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, using batch microwave oven treatment of hepatitis C virus (HCV) and HIV-1 [11], and bacteria [12]- [18] can produce a ≥4log 10 reduction in inactivation. Furthermore, continuous flow microwave oven irradiation has produced similar reductions in bacteria [19] [20] and Virus inactivation [21]. Batch microwave generated stream (MGS) decontamination (within a multi-mode microwave oven) of influenza virus inculcated N95-like respirators have been reported [22]- [27].…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [8], researchers from Air Force Research Laboratory, developed a set of experimental tools capable of presenting electromagnetic waves to an aerosol mixture of biological media and viruses with the capability to vary energy, power, and frequency of the electromagnetic exposure. In [9], the inactivation performance and bactericidal mechanisms for microwave-irradiated waterborne and airborne E-coli were compared. Contreras et al [10], presented the biophysical methods as an impact alternative to more traditional methods based on the investigation for the virus resonance frequency.…”
Section: Introductionmentioning
confidence: 99%